Assessment of the Association of Periodontal Diseases in Pregnant Women and the Efficacy of Periodontal Treatment in the Context of Premature Births and Pregnancy Complications – a Narrative Review - Kranz, Angela; Feierabend, Nathalie; Sliwka, Doreen; Wiesegart, Anja; Abele, Harald; Graf, Joachim (Geburtshilfe und Frauenheilkunde, 2022)
Introduction Periodontal diseases are widespread in women of reproductive potential. Although their treatment of these disorders contributes to oral health, there is still no conclusive evidence that this intervention has a beneficial effect on the course of pregnancy, in particular the rate of premature births. On the one hand, the aim of the paper is a systematic assessment of the association between periodontal diseases and pregnancy complications, based on the current literature. On the other hand, the efficacy of periodontal treatments vs. no treatment in pregnant women should be assessed with the target criterion of premature birth or other pregnancy complications.Materials and methods The narrative review was based on the PRISMA statement. Premature births were defined as primary endpoints, while various perinatal and maternal outcomes were grouped together as secondary endpoints. An electronic database search for relevant meta-analyses and systematic reviews was carried out in PubMed and the Cochrane database. Methodological characteristics and the results of the included studies were extracted. The RR or OR (95% CI) was used to measure the result. The quality of the included studies was assessed according to the AMSTAR checklist.Results Seven publications were included (total number of subjects n = 56755). The majority of included studies do not demonstrate a significant association of periodontal disease and/or periodontal treatment with certain childhood and/or maternal outcomes. The quality of the included studies was deemed to be sufficient.Conclusion Even today, there is insufficient evidence to confirm the correlation between periodontal disease and certain maternal and/or infantile outcomes. Periodontal treatment during pregnancy also does not seem to affect the risks of pregnancy. Nevertheless, it is recommended that all pregnant women are advised to improve their daily oral hygiene in order to prevent inflammatory diseases, regardless of the progress of the pregnancy.Einleitung Parodontalerkrankungen sind bei Frauen im reproduktiven Alter weit verbreitet. Obwohl deren Behandlung zur Mundgesundheit beiträgt, gibt es nach wie vor keine stichhaltigen Beweise dafür, dass diese Intervention den Schwangerschaftsverlauf – insbesondere die Rate an Frühgeburten – günstig beeinflusst. Ziele der Arbeit ist einerseits eine systematische Beurteilung des Zusammenhangs von Parodontalerkrankungen und Schwangerschaftskomplikationen auf dem Stand der aktuellen Literatur. Andererseits soll die Wirksamkeit von Parodontalbehandlungen vs. keiner Behandlung bei schwangeren Frauen mit dem Zielkriterium der Frühgeburt oder anderen Schwangerschaftskomplikationen beurteilt werden.Material und Methoden Das narrative Review orientierte sich am PRISMA-Statement. Als primäres Outcome wurden Frühgeburten festgelegt, als sekundäre Outcomes wurden verschiedene perinatale und maternale Outcomes in einer Gruppe zusammengefasst. In PubMed und der Cochrane-Datenbank wurde eine elektronische Datenbankrecherche nach relevanten Metaanalysen und systematischen Reviews durchgeführt. Es wurden methodische Kennzeichen sowie die Ergebnisse der eingeschlossenen Studien extrahiert. Als Ergebnismaß wurde das RR oder OR (95%-KI) betrachtet. Die Qualität der eingeschlossenen Studien wurde nach der AMSTAR-Checkliste bewertet.Ergebnisse Sieben Publikationen wurden eingeschlossen (Gesamt-Probandinnenanzahl n = 56755). Die Mehrheit der eingeschlossenen Studien weisen keinen signifikanten Zusammenhang einer Parodontalerkrankung und/oder einer Parodontalbehandlung mit bestimmten kindlichen und/oder mütterlichen Outcomes nach. Die Qualität der eingeschlossenen Studien wurde als ausreichend eingestuft.Schlussfolgerung Auch heute gibt es keine ausreichende Evidenz, um den Zusammenhang von Parodontalerkrankungen und bestimmten mütterlichen und/oder kindlichen Outcomes zu bestätigen. Auch scheint eine Parodontalbehandlung in der Schwangerschaft die Schwangerschaftsrisiken nicht zu beeinflussen. Es wird dennoch empfohlen, dass eine Beratung aller Schwangeren zur Verbesserung der alltäglichen Mundhygiene stattfindet, um entzündlichen Krankheiten unabhängig vom Schwangerschaftsverlauf präventiv entgegenzuwirken.
Keywords: Parodontalerkrankungen; Frühgeburt; negative Geburtsoutcomes; Schwangerschaft; Evidenz